Political Leadership in France - Gaffney, J. author. aut Link
XXV, 258 p.
Keywords: Gaffney analyzes how de Gaulle came to power in 1958: The drama surrounding the Fourth Republic's collapse, and the focus upon an exceptional individual meant that de Gaulle was able to confer a particular style of leadership on the Fifth Republic. The five Presidents who came after him have each capitalized on their own political 'persona.'.